PENGARUH PENERAPAN MANAJEMEN RISIKO TERHADAP RETURN SAHAM PERBANKAN BERDASARKAN KELOMPOK BUKU BANK - Nurfauziah Nurfauziah; Sri Mulyati (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
Risk management is part of a comprehensive business strategy with the aim of contributing to protecting and increasing shareholder value. An increase in stock value indicates an increase in stock returns obtained by investors. This study examines the effect of risk management implementation on bank stock returns as seen from the bank book group, namely bank book group 1, bank book group 2, bank book group 3 and bank book group 4. The application of risk management is seen from credit risk, liquidity risk, risk. operational and market risk. The research was conducted on all commercial banks that went public and were active from 2015 to 2019, as many as 44 banks. The results of the study state that: overall (for all bank book groups) the application of risk management, namely credit risk, liquidity risk, operational risk and market risk does not affect stock returns, except for bank book group 1, credit risk and operational risk and market risk for book group 4 has a significant effect on stock returns.